Aurora: Mobile application for analysis of spatial variability of thermal comfort indexes of animals and people, using IDW interpolation - Oliveira Júnior, Arilson José de [UNESP]; Souza, Silvia Regina Lucas de [UNESP]; Dal Pai, Enzo [UNESP]; Rodrigues, Bruno Timóteo [UNESP]; Souza, Valter Cesar de [UNESP] (Elsevier, 2019)
This application note introduces an app for Android smartphones to create maps of the spatial variability of thermal comfort indexes and meteorological parameters. The application was developed through the Java object-oriented programming language, using the integrated Android Studio development environment. The interpolator method employed was the Inverse Distance Weighted (IDW), adopting p = 2. The validations demonstrated that the algorithm is in accordance with the IDW interpolator equation and presented results showed that the maps created by the application can be useful in obtaining diagnoses of the thermal conditions of environments, especially in animal production sheds.
Keywords: Android; IDW; Interpolation of data; Smartphones; Thermal comfort